Slovak Republic : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2002)
This Selected Issues paper and Statistical Appendix investigates the reasons for the large, recurrent external current account deficits in Slovakia, which are unusual by the current standards of other advanced transition economies. The paper examines the implications for external sustainability and reviews the causes of the widening in the external deficit from 2001. It discusses Slovakia's competitiveness and estimates a range for the external current account deficit that could be sustainable in the medium term.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet